Ecomorphology of main food processing structures of four ocypodid species: how do they relate to the crabs’ trophic habits? - Lim, Shirley S. L.; Yong, Adeline Y. P. (Zootaxa, 2024)
The spoon-tipped (ST) setae coverage and their abundance on the second maxillipeds as well as the morphology of the urocardiac and zygocardiac ossicles from the gastric mills of the four ocypodid species, viz., Austruca annulipes (H. Milne Edwards, 1837), Gelasimus vocans (Linnaeus), 1758, two typical deposit-feeding fiddler crabs, Petruca panamensis (Stimpson, 1859), an atypical herbivorous-cum-‘sediment swallower’ fiddler crab, and Ocypode ceratophthalmus (Pallas, 1772), an omnivorous ghost crab, were described and compared in relation to their respective trophic habits. In the three fiddler crabs, ST setae coverage and abundance generally correlated with their habitats’ sediment grain size characteristics—more ST setae in A. annulipes (‘sandy-habitat crab’) and less in G. vocans (‘muddy-habitat crab’). ST setae were absent in O. ceratophthalmus, which suggests that these setae were not needed for food processing. In the two deposit-feeding fiddler crabs, the median tooth of the urocardiac ossicle had tooth-like transverse ridges to grind against the dentition of the lateral teeth of the zygocardiac ossicles. The median tooth in P. panamensis, however, had transverse ridges that resemble that of a vascular plant eater as well as some posterior tooth-like transverse ridges, typically found in deposit feeders; and twice the number of incisors than the other three ocypodids, for cutting up ingested algal pieces. The omnivorous O. ceratopthalmus had four raised transverse ridges on the round blunt median tooth as well as large premolars and molars on the zygocardiac lateral teeth for maceration of animal tissue. Hence, ST setae abundance as well as the grinding surfaces and dentition of the two gastric mill ossicles are indicative of the habitat adaptations and trophic habits respectively.